أثر تطوير المسار المهني في الثقة التنظيمية (دراسة ميدانية عن المصارف الخاصة العاملة في مدينة دمشق) - إسماعيل حسان; وراق أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2016)
This study investigates the impact of career development on the organizational trust. The population of the research consists of the employees in Syrian private banks in Damascus city. A total sample of 400 employees was selected. To achieve the objective of the study, descriptive analysis approach was used. Secondary data were collected from previous studies, books, and other related references. The questionnaire is used as a main tool for collecting the primary data. Data are analyzed by using the Statistical package for social sciences (SPSS). Means and standard deviations are computed, and the linear regression technique is used to test research hypotheses. The main results of the research are: 1. Supervisors contribute reasonably in subordinates’ career development. 2. Supervisor’s contribution in employees’ career development significantly and positively affects supervisor’s and organization’s trust. يهدف هذا البحث إلى دراسة أثر عملية تطوير المسار المهني للعاملين في الثقة التنظيمية وذلك من خلال التركيز على إسهام المشرف في هذه العملية. يتمثل مجتمع البحث بالعاملين في القطاع المصرفي الخاص في مدينة دمشق, وقد بلغت عينة البحث 400 عامل من المصارف الخاصة. لتحقيق أهداف البحث تم الاعتماد على المنهج الوصفي التحليلي, فقد جُمعَت البيانات الثانوية من الدراسات السابقة والمراجع ذات الصلة في حين شكل الاستبيان أداة البحث الرئيسة لجمع البيانات الأولية. حُللِت بيانات الاستبيان ﺒﺎﺴﺘﺨﺩﺍﻡ ﺒﺭﻨﺎﻤﺞ ﺍﻟﺤﺯﻤﺔ ﺍلإﺤﺼﺎﺌﻴﺔ ﻟﻠﻌﻠﻭﻡ الاجتماعية (SPSS) إذ تمّ احتساب قيم المتوسطات الحسابية والانحرافات المعيارية إضافة لاختبار فرضيات البحث من خلال تقنية الانحدار الخطي. توصل البحث إلى مجموعة من النتائج, من أهمها: • يسهم المشرف بشكل مقبول نوعاً ما في تطوير المسار المهني لمرؤوسيه. • يؤثر إسهام المشرف في تطوير المسار المهني للعاملين بشكل معنوي وإيجابي في خلق الثقة بالمشرف وبالمنظمة.